PENGARUH PROFITABILITAS DAN TATA KELOLA PERUSAHAAN TERHADAP NILAI PERUSAHAAN DENGAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY SEBAGAI VARIABEL INTERVENING Studi Empiris pada Perusahaan Sektor Barang Konsumsi Primer yang Terdaftar di Bursa Efek Indonesia Tahun 2019 – 2021 - Hanif Patria Prabantama; Mutiara Tresna Parasetya (Diponegoro Journal of Accounting, 2022)
Increasing Company Value is one of the most important things for a company because it is a measure of the company's success in the eyes of stakeholders. The increase in the value of the company is influenced by many things, considering that the disclosure of company information varies greatly, so it needs to be studied more deeply regarding its effects and characteristics. This study aims to analyze the effect of corporate governance and profitability on firm value through the disclosure of corporate social responsibility.The independent variables in this study are Profitability and Corporate Governance. The dependent variable in this study is firm value, while the intervening variable is CSR disclosure. In accordance with Signaling and Stakeholder Theory, Corporate Governance and Profitability and CSR disclosure have a positive influence on Company Value. The population in this study is the Primary Consumer Goods Sector companies listed on the Indonesia Stock Exchange in 2019 – 2021. The method used in sampling in this study is the Purposive Sampling method using predetermined criteria so as to produce 62 samples of consumer goods companies. The results of statistical tests in this study indicate that Corporate Social Responsibility Disclosure has an effect on firm value and profitability has an effect on firm value. However, Corporate Governance has no effect on Corporate Social Responsibility Disclosures, Profitability has no effect on Corporate Social Responsibility Disclosures, Corporate Governance has no effect on Company Value, , Corporate Governance has no effect on Company Value through Corporate Social Responsibility Disclosures, and Profitability does not influence on Company Value through Corporate Social Responsibility Disclosure